2017
DOI: 10.1124/jpet.117.244392
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 Discrimination: Effects of Endocannabinoids and Catabolic Enzyme Inhibitors

Abstract: An improved understanding of the endocannabinoid system has provided new avenues of drug discovery and development toward the management of pain and other behavioral maladies. Exogenous cannabinoid type 1 (CB) receptor agonists such as Δ-tetrahydrocannabinol are increasingly used for their medicinal actions; however, their utility is constrained by concern regarding abuse-related subjective effects. This has led to growing interest in the clinical benefit of indirectly enhancing the activity of the highly labi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In this regard, neither the nonselective FAAH/MGL inhibitor AM4302 nor the FAAH-selective inhibitor URB597 similarly substituted for AM2389 in precluding rimonabant-lever responding. Although previous work in squirrel monkeys indicates that doses of URB597 and AM4302 studied here are pharmacologically active and that URB597 alone does not produce CB1-like effects (Justinova et al, 2008;Leonard et al, 2017), it remains possible that rimonabant-lever responding might have been attenuated by higher doses of AM4302. For example, Leonard et al (2017) showed that AM4302, like other nonselective FAAH/MGL inhibitors, is fully capable of producing a CB 1 discriminative stimulus in agonist-trained subjects.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this regard, neither the nonselective FAAH/MGL inhibitor AM4302 nor the FAAH-selective inhibitor URB597 similarly substituted for AM2389 in precluding rimonabant-lever responding. Although previous work in squirrel monkeys indicates that doses of URB597 and AM4302 studied here are pharmacologically active and that URB597 alone does not produce CB1-like effects (Justinova et al, 2008;Leonard et al, 2017), it remains possible that rimonabant-lever responding might have been attenuated by higher doses of AM4302. For example, Leonard et al (2017) showed that AM4302, like other nonselective FAAH/MGL inhibitors, is fully capable of producing a CB 1 discriminative stimulus in agonist-trained subjects.…”
Section: Discussionmentioning
confidence: 75%
“…Although previous work in squirrel monkeys indicates that doses of URB597 and AM4302 studied here are pharmacologically active and that URB597 alone does not produce CB1-like effects (Justinova et al, 2008;Leonard et al, 2017), it remains possible that rimonabant-lever responding might have been attenuated by higher doses of AM4302. For example, Leonard et al (2017) showed that AM4302, like other nonselective FAAH/MGL inhibitors, is fully capable of producing a CB 1 discriminative stimulus in agonist-trained subjects. Based on the potency relationship in the two types of discrimination studies discussed above, considerably higher doses of AM4302 than those tested here may be necessary to reduce rimonabant-lever responding.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is a curious gap considering the limitations of rodent subjects in emesis research and substantial in vivo cannabinoid research that has been conducted in nonhuman primates. In particular, squirrel monkeys, in which cannabinoids have been extensively studied (e.g., Branch et al, 1980;Tanda et al, 2000;Justinova et al, 2003Justinova et al, , 2013Solinas et al, 2007;Kangas and Bergman, 2012;Desai et al, 2013;Kangas et al, 2013Kangas et al, , 2016Leonard et al, 2017) and which have an emetic response, are highly suitable for evaluating the antiemetic effects of cannabinoids. The present studies therefore examined D 9 -THC, the primary psychoactive constituent in cannabis, and methanandamide [mAEA; (R)-(+)-arachidonyl-19-hydroxy-29-propylamide], a metabolically stable analog of the endocannabinoid anandamide, for their ability to block emesis and prodromal hypersalivation in the squirrel monkey.…”
Section: Introductionmentioning
confidence: 99%
“…When mixed with N-linoleoylethanolamide and N-oleoylethanolamide from cacao, which inhibit anandamide breakdown, the levels of endogenous anandamide are augmented further. When breakdown of anandamide is inhibited pharmacologically or genetically, anandamide is able to produce a state of intoxication similar to tetrahydrocannabinol in rodents and nonhuman primates (2729). Thus, I suggest that chili peppers and vanilla were not chosen coincidentally or haphazardly as flavorings but precisely because, together, they were able to achieve high levels of anandamide.…”
Section: Introductionmentioning
confidence: 99%